2018
DOI: 10.1007/s00167-018-5003-6
|View full text |Cite
|
Sign up to set email alerts
|

Italian consensus statement for the use of allografts in ACL reconstructive surgery

Abstract: IV, consensus of experts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…35 Especially in case of multiple failures and when peripheral reconstructions are needed, the use of allograft is strongly reccomended. 31,36 In our experience, we have used a prevalence of autograft BPTB and allograft as graft for the last revision surgery. Albeit the literature shows very good results with both kinds of graft and indicate autograft BPTB as the gold standard, 35 several authors reported a higher failure rate using allograft in comparison to autograft.…”
Section: Discussionmentioning
confidence: 99%
“…35 Especially in case of multiple failures and when peripheral reconstructions are needed, the use of allograft is strongly reccomended. 31,36 In our experience, we have used a prevalence of autograft BPTB and allograft as graft for the last revision surgery. Albeit the literature shows very good results with both kinds of graft and indicate autograft BPTB as the gold standard, 35 several authors reported a higher failure rate using allograft in comparison to autograft.…”
Section: Discussionmentioning
confidence: 99%
“…This could allow an earlier return to levels of activity. Particularly, graft choice by the surgeons changed in the more recent studies to the use of allografts in older and less active patients, which correlated with a significant decrease in risk of graft failure [2, 5, 28].…”
Section: Discussionmentioning
confidence: 99%
“…In order to be considered for inclusion, studies needed to include: (1) patients with a minimum age of 40 years undergoing a primary ACL reconstruction; (2)…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…Anterior cruciate ligament reconstruction (ACLR) with the patient’s own autograft tissue (hamstring or bone patellar tendon bone) is the most common surgical technique to treat ACL complete rupture. Allografts are commonly used in revision and multiligament surgery [ 30 ]; albeit, in the last decades, their use also in primary ACLR is growing [ 1 , 13 , 36 ].…”
Section: Introductionmentioning
confidence: 99%